A method to calculate evaporation and evapo- transpiration in Iraq - HASSAN, HASSANA; AZAKI, NATIQ; ISSA, HALA (MAUSAM, 1987)
A method is presented to calculate potential evapotranspiration (PE), free surface water evaporation (E0) and pan evaporation (EPAN). The values of these parameters obtained show highly significant correlation and good agreement with the available actual measurements, The values obtained for these parameters by other different empirical formulae are found to be higher than the actual measurements.